Agent Technology in Hotel Business - KOZLOV, Dmitry Aleksandrovich (Journal of Environmental Management and Tourism, 2017)
The main aim of this paper is to analyze the possible ways of using of agent technology in hotel business on the example of Russian Federation. According to key findings, Russian hotel market has seven distinct states. The occurrence of next state can be predicted so we have some kind of decision-making system or early warning system. In addition, characteristics of these states may be used as a target (potential) in revenue management system of hotel enterprise instead of rack rate and maximum occupancy. Presently it is necessary to understand that complex research methods would be used for forecasting and decision-making in modern economic conditions. So, agent technology can be a good solution for understandings of hidden relationships and finding optimal response in hospitality and tourism.